The situation of the import and export of vegetables in Romania in the period 2007-2016 - Marius Mihai Micu; Ana-Ruxandra Micu; Ionuţ Daniel Petre (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
The state of import and export of fresh vegetables in Romania presents major imbalances, which tend to increase from year to year. Even if it is a vegetable-growing country, Romania imports fresh vegetables from countries like Turkey, the Netherlands or Italy, countries with a tradition of growing vegetables and significant areas of protected areas, benefiting from the benefits of this way of cultivating vegetables. In the present paper, using the technical-economic method of the comparison, based on the statistical data, an analysis was made of the areas cultivated with vegetables in the 8 regions of Romania, according to the main crop systems, the production made, as well as the quantities imported and exported.
Keywords: Q17; 330; vegetables; import; export